Pengalaman Orang Tua dengan Anak Kemungkinan Attention Deficit Hyperactivity Disorder pada Usia Pra Sekolah - Prima Daniyati Kusuma; Arni Nur Rachmawati; Maryanti; Dwi Budi Utami; Yeni Restiana (LPPM STIKES NOTOKUSUMO YOGYAKARTA, 2015)
Background: Attention Deficit Hyperactivity Disorder (ADHD) is a common disorder in child behavioral disorders. This disorder is characterized by the inability of the child to focus on something that is encountered, so that his attention span is very short compared to other children the same age. Not many parents, teachers, or people who understand these disorders so that children with ADHD tend to get treatment and handling erroneous. Objective: Explore experiences of parents with children possibility of ADHD in preschool. Method:Qualitative research with phenomenological approach and the use of informants as many as 5 people. Result: Knowledge about behavior of parents of ADHD had good chances. Parents sufficient experience barriers to care for the child and the needs of various efforts to overcome obstacles in the treatment of children with possible ADHD. Conclusion: Each parent has a different knowledge on ADHD that have different ways of dealing with the behavior of children with ADHD possibilities.